PENERAPAN NILAI KODE ETIK KEDOKTERAN INDONESIA PADA ERA JAMINAN KESEHATAN NASIONAL DI KABUPATEN BENGKALIS - Sarah Miftahul Rahmi; Dedi Afandi; Lilly Haslinda (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTEvery doctors in Indonesia ought to have values and norms held by Kode Etik Kedokteran Indonesia (KODEKI). These values applied when giving health services to patient moreover after Jaminan Kesehatan Nasional (JKN) program has been implemented since 1st January 2014. This causes general practitioners to work more especially in the primary health facilities or fasilitas kesehatan tingkat pertama (fktp). This program has been implemented all over Indonesia which includes Bengkalis Regency. The aim of the research was to determine implementation of KODEKI values in JKN era in Bengkalis Regency. Design used in this research was exploration method with qualitative approach. Informants were selected using snowball sampling who met inclusion criteria and were willing to be interviewed. There were 4 informants selected. Researcher did direct interview with the informants using guidelines of question and the data were recorded using audio recorder. The result showed that all of the informants possess altruism, responsibility, professional idealism, accountability, scientific integrity and social integrity. Thus, it can be concluded that general practitioners in Bengkalis Regency hold true to KODEKI values in JKN era. In additional to the answers of the informants, this result was supported by daily attitudes shown by the doctors towards society.Keywords : KODEKI values, JKN, Bengkalis Regency